Cost investigation of multihoming-based scheme to support mobility management in NEMO - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Hasan, Mohammad Kamrul (Institute Mathematical Sciences, Universiti Putra Malaysia, 2016)
Network Mobility Basic Support Protocol (NEMO BSP) is an augmentation of Mobile IPv6 in which a frequent notification are required to update current location of the Mobile Router (MR) to maintain Internet connectivity during inter handoff through preserving the Binding Updates (BU). It might be designed in a high speed train, car as well as aircrafts with a vast range of consigned IP backbone. Nevertheless, NEMO BSP inherits some of the shortcomings like higher handoff latency with packet loss and fails to ensure seamless handover. Moreover, a longer time is required to complete inter Handoff for mobile environment,which may cause performance degradation for the applications are mainly Voice over IP (VoIP), video streaming that running on Mobile Network Nodes (MNNs). This consequence is particularly considerable in wireless environment. As a result, it can be retain seamless Internet connectivity through using multiple network interfaces in NEMO. In this paper, a general overview on existing multihoming-based scheme in NEMO is given in an integrated manner. Furthermore, it estimates Cost Ratio (CR) through numerical analysis in order to support mobility management.